Prespektif Hukum Apabila Karyawan Melanggar Employee Branding - Santoso, Joe Martin; Ambarwati, Mega Dewi (Media Hukum Indonesia (MHI), 2025)
Employee branding is a marketing strategy for companies that focuses on how employees perceive, feel, and represent the company's brand, both inside and outside the organization. This is an effort to create a positive image of the company in the eyes of employees and motivate them to become active brand ambassadors. of employee branding is to build a positive image of the company in the eyes of employees, which in turn will increase their loyalty, retention, and productivity. Employees who feel proud of their place of work will be more motivated to give their best and voluntarily promote the company to others. There is a violation of cause and effect if you do not do Employee Branding.